Clustering Residents' Intention and Behavior Toward Forest Rehabilitation Initiative: a Case Study in The Upstream of Central Java, Indonesia - Arum Puspaningtyas Manto; Prasetyo Nugroho (Jurnal Manajemen Hutan Tropika, 2022)
The success of forest rehabilitation initiatives depends on community engagement; thus, it is important to understand community opinions toward forest rehabilitation initiatives. However, the available literature is sparse, as most research focuses on forest rehabilitation research, frequently only on planting performance. We scrutinized residents' opinions of the forest rehabilitation initiative using the extended Theory of Planned Behavior framework variables, i.e., behavior (B), behavioral intention (BI), attitude toward behavior (ATB), perceived behavioral control (PBC), subjective norm (SN), moral norm (MN), perceived risk (PR), and self-identity (SI). Those factors were used to cluster residents into various groups using the k-means clustering method. 307 completed questionnaires were obtained. We found that residents were clustered into two distinctive groups: active supporters (AS) and passive supporters (PS). PS was dominant in the community (61.9%). They were characterized by less agreement in perceiving the adverse impacts of forest degradation, less intent and engagement in forest rehabilitation programs. In contrast, AS was more receptive to forest rehabilitation initiatives. These results confirm that residents are heterogeneous in opinions and interest in forest rehabilitation initiatives. Therefore, forest managers should design effective policies and alternative approaches to ensure the success of forest rehabilitation programs based on those distinctive groups.